Avian metapneumovirus: A five-plex digital droplet RT-PCR method for identification of subgroups A, B, C, and D - Lemaitre, Evelyne; Bougeard, Stéphanie; Allée, Chantal; Eterradossi, Nicolas; Courtillon, Céline; Brown, Paul Alun (Frontiers in Veterinary Science, 2022)
End-point and real-time avian metapneumovirus (AMPV) RT-PCRs have been developed to detect one or two of the four recognized subgroups (A,B,C and D) simultaneously or for broad range AMPV detection. Current subgroup specific tests target variable areas of the genome which makes these PCRs sensitive to specificity defects as recently documented. In the current study, a single 5-plex digital droplet RT-PCR targeting the conserved viral polymerase gene of AMPV, which is less prone to genetic drift, has been designed. This digital droplet RT-PCR was capable of identifying each of the four AMPV subgroups. Each subgroup was identified according to a specifically assigned fluorescent amplitude. Specificity, which was tested including 31 AMPV strains, non-AMPV avian viruses and closely related human respiratory viruses, was 100%. The specific limit of detection for extracted viral RNA was estimated between 1 to 3 copies/µl. This tool simplifies the number of tests required for AMPV genotype diagnostics and should be theoretically less effected by viral genome evolution due to its target region. Ultimately, application of this test will contribute to an improved understanding of the global geographic distribution and subgroup host range of field strains.